Integrating ethical sensitivity through religiosity in accounting education - Jaspal, S. J. S. *; Muhammad, Sadiq; Kamaljeet, K. (Growing Science, Canada, 2020)
Accounting is part of everyone’s life and affects all stakeholders who are the users of the accounting information. Organizations are created to serve their stakeholders and governments are supposed to govern, regulate and safe guard the interests of these stakeholders. Whilst accounting frequently experiences behavioral and human governance issues, this study explores the level of ethical sensitivity and its relationship with religiosity among final year accounting students in Malaysia. This study addresses the lack and the need to inculcate religiously orientated topics to be embedded and inculcated in the syllabi of bachelor of accounting, because being intrinsically religious makes an individual ethical. A quantitative research method is applied where questionnaires are administered to final year undergraduate accounting students at selected public and private universities in Malaysia. This study utilized Shaub’s ethical sensitivity questionnaire to measure ethical sensitivity and Allport’s Religiosity Orientation Scale to measure religiosity. Students are found to be ethically sensitive and by using Binary Logistic Regression, it is concluded that ethical sensitivity is influenced by intrinsic religiosity but not influenced by social extrinsic religiosity and personal extrinsic religiosity and may give some insights to the prospective employer on the selection criteria of future accountants and auditors, with regards to ethical conduct.